2022
DOI: 10.1155/2022/5802217
|View full text |Cite
|
Sign up to set email alerts
|

High-Performance Concrete Strength Prediction Based on Machine Learning

Abstract: High-performance concrete is a new high-tech concrete, produced using conventional materials and processes, with all the mechanical properties required for concrete structures, with high durability, high workability, and high volume stability of the concrete. The compressive strength of high-performance concrete has exceeded 200 MPa. 28-d average strength between 100 to 120 MPa of high-performance concrete has been widely used in engineering. Compressive strength is one of the important parameters of concrete,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Ref. [21] applied Random Forest, Support Vector Regression, and XGBoost to predict the resistance of high-performance concrete, finding XGBoost to be the most accurate. The artificial neural network, decision trees, and random forest methods for predicting tensile splitting strength were described in the study by [22], where concrete is used as a recycled aggregate, obtaining a database divided into training and validation.…”
Section: Related Workmentioning
confidence: 99%
“…Ref. [21] applied Random Forest, Support Vector Regression, and XGBoost to predict the resistance of high-performance concrete, finding XGBoost to be the most accurate. The artificial neural network, decision trees, and random forest methods for predicting tensile splitting strength were described in the study by [22], where concrete is used as a recycled aggregate, obtaining a database divided into training and validation.…”
Section: Related Workmentioning
confidence: 99%
“…Experimental prediction results show that the developed data-driven neural network prediction model can provide rapid prediction and design for FRP-constrained composites. Moreover, some researchers [38][39][40] also used machine learning methods to predict the strength and self-healing behavior of concrete and have obtained good prediction results.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that the RF method was able to predict compressive strength with high accuracy. Liu [ 41 ] investigated the prediction of the mechanical properties of HPC using extreme gradient boosting (XGBoost), SVR, and RF. He showed that the XGBoost algorithm has appropriate performance in predicting the compressive strength of HPC.…”
Section: Introductionmentioning
confidence: 99%